Application of a magnetic biomass-based photocatalytic porous carbon material and preparation method thereof
Patent Information
- Application Number
- CN202610682773.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-18
- Publication Date
- 2026-10-13
AI Technical Summary
[0008]为了解决现有技术中存在的技术问题,本发明提供了一种多级分区协同结构的磁性光催化多孔碳复合材料及其制备方法与应用,以解决现有技术中存在的活性组分分布无序、Fe元素形态单一、孔道方向性不可控、活性组分与碳基体结合力弱、功能协同不足、高盐环境下孔道易塌缩等问题,实现吸附富集-光催化降解-类芬顿催化-磁分离回收-抗高盐孔道塌缩的多场耦合协同
1.本发明利用ZIF-8尺寸筛分效应使TiO2形成外层梯度富集壳层,通过Ti-O-P和Ti-N界面键原位化学锚定,脱落率<5%;采用冻结模板主动造孔,构建微孔-介孔-宏孔分级定向贯通孔道,降低传质阻力;
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of porous carbon materials technology, specifically relating to a multi-level partitioned synergistic structure of a magnetic photocatalytic biomass-based porous carbon composite material, its preparation method, and its application. Background Technology
[0002] With the acceleration of industrialization, the discharge of oily wastewater, organic dye wastewater and high-salt industrial wastewater continues to increase, posing a serious threat to the aquatic ecological environment and human health. Among various water pollution control technologies, adsorption is widely used due to its ease of operation. However, traditional adsorbents have problems such as easy secondary pollution after adsorption saturation and difficulty in recycling. Photocatalysis technology can completely mineralize organic pollutants into CO2 and H2O, but conventional TiO2 photocatalysts have defects such as narrow light response range, easy recombination of photogenerated carriers, and difficulty in recycling powdered catalysts.
[0003] Integrating adsorption and photocatalysis into a single material to achieve integrated "adsorption-degradation" treatment of pollutants has become an important development direction in this field; however, existing composite photocatalytic adsorption materials still face the following key challenges in practical applications: (i) At the structural design level, the active components are distributed in a disordered manner and lack synergy between different zones. Most existing biomass carbon-based photocatalytic materials have active components randomly distributed in the carbon skeleton. TiO2 and Fe species do not form a gradient structure or zone configuration, which limits the light absorption efficiency and lacks synergy between different functional components.
[0004] (ii) At the Fe element morphology level, there is a single morphology and insufficient functional synergy; in the existing technology, Fe element mostly exists in the form of doped ions or single oxides, without an independent magnetic phase, the material cannot achieve magnetic recovery, and does not have Fenton-like catalytic activity, and its performance drops sharply under light-free conditions.
[0005] (iii) At the level of pore structure, the directionality of the pores is uncontrollable and the mass transfer resistance is large; the pores of existing porous materials are mostly randomly distributed and lack directional continuity. In high-salt environments, the pores are prone to collapse and the performance is greatly reduced.
[0006] Based on the above analysis, existing technologies generally suffer from defects such as disordered structure, single Fe morphology, uncontrollable pore directionality, weak binding force of active components, insufficient functional synergy, and poor adaptability to high-salt environments. Developing a multifunctional integrated composite material that achieves substantial innovation in three aspects—structural design, preparation process, and mechanism of action—has become an urgent need in this field.
[0007] Meanwhile, with the widespread application of electronic devices and the development of radar detection technology, electromagnetic wave absorbing materials have also shown important application value in the fields of civilian electromagnetic shielding and military stealth. However, existing wave absorbing materials and photocatalytic materials have significant differences in application scenarios and functional requirements, and research on integrating the functions of the two into the same material has not been reported. Based on the realization of the above-mentioned photocatalytic material, this application discovers that the material also has electromagnetic wave absorption properties, providing a new idea for its multifunctional applications. Summary of the Invention
[0008] To address the technical problems existing in the prior art, this invention provides a multi-level partitioned synergistic magnetic photocatalytic porous carbon composite material, its preparation method, and its application. This invention solves the problems existing in the prior art, such as disordered distribution of active components, single morphology of Fe element, uncontrollable pore directionality, weak bonding force between active components and carbon matrix, insufficient functional synergy, and easy collapse of pores under high salt conditions. It achieves multi-field coupling synergy of adsorption enrichment, photocatalytic degradation, Fenton-like catalysis, magnetic separation and recovery, and resistance to high salt pore collapse.
[0009] This invention employs a phased construction method involving MOF in-situ growth, frozen template-directed pore formation, and cold plasma-assisted in-situ phosphating. This method in-situ composites outer-layer gradient-enriched TiO2 nanoparticles and inner-layer distributed high-entropy metal phosphide (HEP) nanoparticles onto a three-dimensional, directionally interconnected nitrogen / phosphorus co-doped porous carbon framework. Furthermore, Fe is incorporated as the Fe component within the HEP and interacts with Fe-N... x Dual-morphological coexistence at single-atom sites; To achieve the above objectives, the technical solution adopted by the present invention is as follows: 1. Alkali soaking Plant fiber raw materials are soaked in an alkaline solution of 10-30 times their weight at 40-60℃ for 2-5 hours. After soaking, the raw materials are washed and dried to obtain alkaline-impregnated fibers. The plant fiber is one or more of the following: paulownia wood fiber, cotton fiber, hemp fiber, and straw fiber. The length of the plant fiber is 2-10 mm and the diameter is 0.1-1 mm. The alkaline solution is a sodium hydroxide or potassium hydroxide solution with a mass concentration of 4-6 wt%. Preferably, the soaking temperature is 50°C and the soaking time is 3 hours.
[0010] 2. MOF in situ growth Alkali-impregnated fibers were immersed in a metal salt solution and soaked at room temperature for 2-4 hours. After being removed and drained, they were immersed in an organic ligand solution and allowed to stand at room temperature for 12-24 hours. After the reaction was completed, the fibers were removed, washed three times with anhydrous methanol, and dried at 60°C to constant weight to obtain ZIF-8 nanocrystalline fibers. The mass ratio of the alkali-impregnated fiber to zinc nitrate is 1:0.2-0.5; The molar ratio of zinc nitrate to 2-methylimidazole is 1:4-8; The method for preparing the metal salt solution is as follows: zinc nitrate Zn(NO3)2·6H2O or zinc acetate is added to anhydrous methanol and stirred evenly to obtain a metal salt solution with a concentration of 0.02-0.05 mol / L. The organic ligand solution is prepared by dissolving 2-methylimidazole in anhydrous methanol to obtain an organic ligand solution with a concentration of 0.16-0.40 mol / L.
[0011] 3. Precursor impregnation Add titanium precursor, multi-metal precursor, phosphorus-containing organic matter, and nitrogen-containing organic matter to anhydrous methanol or anhydrous ethanol, stir evenly, and then ultrasonically disperse for 15-30 min. The ultrasonic power is 100-300 W and the ultrasonic frequency is 40-80 kHz. After ultrasonic dispersion, a precursor impregnation solution is obtained. Immerse ZIF-8 nanocrystalline fibers in the precursor impregnation solution. The mass ratio of ZIF-8 nanocrystalline fibers to precursor impregnation solution is 1:5-20. Soak at room temperature for 3-6 h, then remove and drain to obtain precursor impregnated fibers. The titanium precursor is tetrabutyl titanate or isopropyl titanate, and the volume fraction of the titanium precursor in the precursor impregnation solution is 10%-30%. The multi-metal precursor is at least four of the following: iron salt, cobalt salt, nickel salt, copper salt, and zinc salt. Each salt is added in an equimolar ratio, and the total metal ion concentration is 0.05-0.2 mol / L. The iron salt is one of ferric nitrate (Fe(NO3)3·9H2O), ferric acetylacetone (Fe(C5H7O2)3), or ferric chloride (FeCl3·6H2O); the cobalt salt is cobalt nitrate (Co(NO3)2·6H2O) or cobalt acetate (Co(CH3COO)2·4H2O); the nickel salt is nickel nitrate (Ni(NO3)2·6H2O) or nickel acetate (Ni(CH3COO)2·4H2O); the copper salt is copper nitrate (Cu(NO3)2·3H2O) or copper acetate (Cu(CH3COO)2·H2O); and the zinc salt is zinc nitrate (Zn(NO3)2·6H2O) or zinc acetate (Zn(CH3COO)2·2H2O). The phosphorus-containing organic matter is phytic acid or triphenyl phosphate, and the amount added is 1-5% of the total mass of the precursor impregnation solution. The nitrogen-containing organic compound is urea, melamine, or polyaniline, and the amount added is 1-5% of the total mass of the precursor impregnation solution.
[0012] 4. Freeze Precursor-impregnated fibers are placed in a polytetrafluoroethylene mold, and deionized water is added to wet the fiber surface. The mass ratio of deionized water to precursor-impregnated fibers is 1:4-5. Then, the mold is placed in a directional freezing device with the cold source located at the bottom of the mold. Directional freezing is performed at a cooling rate of 1-10℃ / min in a direction perpendicular to the cold source. The freezing endpoint temperature is -20 to -196℃. After freezing, the mold is transferred to a freeze dryer and freeze-dried at -50℃ and a vacuum degree of 1-10Pa for 24-48 hours. After freeze-drying, frozen fibers are obtained.
[0013] 5. In-situ phosphating and carbonization The frozen fiber was placed in a dielectric barrier discharge cold plasma reactor. After evacuating the reactor to a pressure of 1-10 Pa, an Ar / H2 mixed atmosphere or an Ar / NH3 mixed atmosphere was introduced to maintain the pressure inside the reactor at 10-100 Pa. The plasma power supply was turned on, and the plasma power was set to 50-200 W. The treatment time was 30-120 min. During the treatment, the temperature inside the reactor was controlled to be ≤400℃. After the treatment was completed, the plasma power supply was turned off, and the protective atmosphere of argon was continued to be introduced until the reactor cooled naturally to room temperature. The fiber was then removed to obtain the magnetic photocatalytic porous carbon composite material.
[0014] When introducing an Ar / H2 mixed atmosphere, the flow rate of the mixed atmosphere is 20-100 sccm, and the volume fraction of H2 is 5%-15%. When introducing an Ar / NH3 mixed atmosphere, the flow rate of the mixed atmosphere is 20-100 sccm, and the volume fraction of NH3 is 5%-10%.
[0015] Compared with the prior art, the present invention has the following advantages and technical effects: 1. This invention utilizes the ZIF-8 size sieving effect to form an outer gradient enriched shell of TiO2, which is chemically anchored in situ through Ti-OP and Ti-N interface bonds, with a shedding rate of <5%; and adopts a frozen template to actively create pores, constructing a hierarchical directional interconnected channel of micropores-mesopores-macropores, thereby reducing mass transfer resistance. 2. First-ever coexistence of Fe in two forms: High-entropy metal phosphides provide magnetic response and co-catalytic function; Fe-N X Single-atom sites impart Fenton-like catalytic activity, with a degradation rate of ≥40% under light-free conditions; 3. This invention employs cold plasma-assisted in-situ phosphating and carbonization, simultaneously completing carbonization, TiO2 crystallization, HEP generation, and Fe-N in one step. x Formation, N / P co-doping and interfacial bond construction, low-temperature retention of directional channels, and in-situ phosphating to ensure uniform HEP distribution; 4. This invention achieves all-weather synergy of four functions: adsorption, photocatalysis, Fenton-like process, and magnetic recovery, while also possessing wave absorption properties. The resulting composite material has a specific surface area >375 m². 2 / g, saturation magnetization ≥6.8 emu / g; after soaking in artificial seawater for 30 days, the specific surface area retention rate is ≥85%, and the photocatalytic degradation rate retention rate is ≥80%, solving the problem of high salt collapse of traditional porous materials. Attached Figure Description
[0016] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments of this application and their descriptions are used to explain this application and do not constitute an undue limitation of this application.
[0017] Figure 1 Scanning electron microscope (SEM) image of the magnetic biomass-based photocatalytic porous carbon material prepared in Example 1; Figure 2 This is a schematic diagram of the structure of the magnetic biomass-based photocatalytic porous carbon material prepared in Example 1; Figure 3 Line graph showing the adsorption efficiency versus oil mass of the magnetic biomass-based photocatalytic porous carbon material prepared in Example 1 during the photocatalytic oil adsorption and decomposition experiment. Detailed Implementation
[0018] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0019] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, regarding numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed.
[0020] The present invention also includes any stated value or intermediate value within a stated range, as well as every smaller range between any other stated value or intermediate value within said range. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0021] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe the methods and materials associated with those references. In the event of any conflict with any incorporated reference, the contents of this specification shall prevail.
[0022] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0023] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0024] This invention uses plant fibers as raw materials, and through alkaline leaching for impurity removal, in-situ growth in ZIF-8, multi-component impregnation containing titanium / multi-metal / phosphorus / nitrogen, frozen template directional pore formation, and cold plasma-assisted in-situ phosphating and carbonization, a multi-level partitioned synergistic magnetic photocatalytic porous carbon composite material is obtained. The resulting material has a hierarchical directional interconnected pore framework with nitrogen / phosphorus co-doped structure, a gradient enrichment of TiO2 on the outer layer, and a high-entropy metal phosphide (HEP) inner layer distribution. Fe is distributed as the Fe component in HEP and Fe-N x Single-atom sites with dual-mode coexistence; HEP endows the material with magnetic and co-catalytic functions, and forms a Z-shaped heterojunction with TiO2 to promote carrier separation; Fe-N x The site endows Fenton-like activity, enabling all-weather degradation; cold plasma low-temperature carbonization preserves directional channels, giving it resistance to high-salt collapse; this material integrates adsorption, photocatalysis, Fenton-like activity, and magnetic recovery, solving problems such as secondary pollution, difficult recycling, and performance degradation in high-salt environments of traditional materials.
[0025] A method for preparing a magnetic biomass-based photocatalytic porous carbon material as an adsorbent includes the following steps: 1. Alkali soaking Plant fiber raw materials are soaked in an alkaline solution of 10-30 times their weight at 40-60℃ for 2-5 hours. After soaking, the raw materials are washed and dried to obtain alkaline-impregnated fibers. The plant fiber is one or more of the following: paulownia wood fiber, cotton fiber, hemp fiber, and straw fiber. The length of the plant fiber is 2-10 mm and the diameter is 0.1-1 mm. The alkaline solution is a sodium hydroxide or potassium hydroxide solution with a mass concentration of 4-6 wt%. Preferably, the soaking temperature is 50°C and the soaking time is 3 hours.
[0026] 2. MOF in situ growth All the alkaline-impregnated fibers obtained in step 1 were immersed in a metal salt solution and soaked at room temperature for 2-4 hours. After being removed and drained, they were immersed in an organic ligand solution and allowed to stand at room temperature for 12-24 hours. After the reaction was completed, the fibers were removed, washed three times with anhydrous methanol, and dried at 60°C to constant weight to obtain ZIF-8 nanocrystalline fibers. The mass ratio of the alkali-impregnated fiber to zinc nitrate is 1:0.2-0.5; The molar ratio of zinc nitrate to 2-methylimidazole is 1:4-8; The method for preparing the metal salt solution is as follows: zinc nitrate Zn(NO3)2·6H2O or zinc acetate is added to anhydrous methanol and stirred evenly to obtain a metal salt solution with a concentration of 0.02-0.05 mol / L. The organic ligand solution is prepared by dissolving 2-methylimidazole in anhydrous methanol to obtain an organic ligand solution with a concentration of 0.16-0.40 mol / L.
[0027] 3. Precursor impregnation Add titanium precursor, multi-metal precursor, phosphorus-containing organic matter, and nitrogen-containing organic matter to anhydrous methanol or anhydrous ethanol, stir evenly, and then ultrasonically disperse for 15-30 min. The ultrasonic power is 100-300 W and the ultrasonic frequency is 40-80 kHz. After ultrasonic dispersion, a precursor impregnation solution is obtained. Immerse ZIF-8 nanocrystalline fibers in the precursor impregnation solution. The mass ratio of ZIF-8 nanocrystalline fibers to precursor impregnation solution is 1:5-20. Soak at room temperature for 3-6 h, then remove and drain to obtain precursor impregnated fibers. The titanium precursor is tetrabutyl titanate or isopropyl titanate, and the volume fraction of the titanium precursor in the precursor impregnation solution is 10%-30%. The multi-metal precursor is at least four of the following: iron salt, cobalt salt, nickel salt, copper salt, and zinc salt. Each salt is added in an equimolar ratio, and the total metal ion concentration is 0.05-0.2 mol / L. The iron salt is one of ferric nitrate (Fe(NO3)3·9H2O), ferric acetylacetone (Fe(C5H7O2)3), or ferric chloride (FeCl3·6H2O); the cobalt salt is cobalt nitrate (Co(NO3)2·6H2O) or cobalt acetate (Co(CH3COO)2·4H2O); the nickel salt is nickel nitrate (Ni(NO3)2·6H2O) or nickel acetate (Ni(CH3COO)2·4H2O); the copper salt is copper nitrate (Cu(NO3)2·3H2O) or copper acetate (Cu(CH3COO)2·H2O); and the zinc salt is zinc nitrate (Zn(NO3)2·6H2O) or zinc acetate (Zn(CH3COO)2·2H2O). The phosphorus-containing organic matter is phytic acid or triphenyl phosphate, and the amount added is 1-5% of the total mass of the precursor impregnation solution. The nitrogen-containing organic compound is urea, melamine, or polyaniline, and the amount added is 1-5% of the total mass of the precursor impregnation solution.
[0028] 4. Freeze Precursor-impregnated fibers are placed in a polytetrafluoroethylene mold, and deionized water is added to wet the fiber surface. The mass ratio of deionized water to precursor-impregnated fibers is 1:4-5. Then, the mold is placed in a directional freezing device with the cold source located at the bottom of the mold. Directional freezing is performed at a cooling rate of 1-10℃ / min in a direction perpendicular to the cold source. The freezing endpoint temperature is -20 to -196℃. After freezing, the mold is transferred to a freeze dryer and freeze-dried at -50℃ and a vacuum degree of 1-10Pa for 24-48 hours. After freeze-drying, frozen fibers are obtained.
[0029] 5. In-situ phosphating and carbonization The frozen fiber was placed in a dielectric barrier discharge cold plasma reactor. After evacuating the reactor to a pressure of 1-10 Pa, an Ar / H2 mixed atmosphere or an Ar / NH3 mixed atmosphere was introduced to maintain the pressure inside the reactor at 10-100 Pa. The plasma power supply was turned on, and the plasma power was set to 50-200 W. The treatment time was 30-120 min. During the treatment, the temperature inside the reactor was controlled to be ≤400℃. After the treatment was completed, the plasma power supply was turned off, and the protective atmosphere of argon was continued to be introduced until the reactor cooled naturally to room temperature. The fiber was then removed to obtain the magnetic photocatalytic porous carbon composite material.
[0030] When introducing an Ar / H2 mixed atmosphere, the flow rate of the mixed atmosphere is 20-100 sccm, and the volume fraction of H2 is 5%-15%. When introducing an Ar / NH3 mixed atmosphere, the flow rate of the mixed atmosphere is 20-100 sccm, and the volume fraction of NH3 is 5%-10%.
[0031] The technical solution of the present invention will be further illustrated by the following embodiments, but the scope of protection of the present invention is not limited thereto; unless otherwise specified, the raw materials used in the following embodiments are all commercially available analytical grade, and the water used is deionized water.
[0032] Example 1 A method for preparing a magnetic biomass-based photocatalytic porous carbon material, comprising the following steps: 1. Alkali soaking Take 5g of paulownia wood fiber (5mm in length and 0.5mm in diameter), place it in 100mL of 1mol / L NaOH solution, soak it at 50℃ for 3h, wash it with deionized water until neutral, and dry it at 60℃ to obtain alkali-impregnated fiber.
[0033] 2. In situ growth 1.2 g Zn(NO3)2·6H2O and 2.6 g 2-methylimidazole were dissolved in 50 mL of anhydrous methanol, respectively. After mixing, the mixture was stirred for 5 min to obtain metal salt solution and organic ligand solution, respectively. The alkali-impregnated fiber was immersed in a metal salt solution and soaked at room temperature for 3 hours. After being removed and drained, it was then immersed in an organic ligand solution and allowed to stand at room temperature for 20 hours. After being removed, it was washed three times with anhydrous methanol and dried at 60°C to constant weight to obtain ZIF-8 nanocrystalline fibers.
[0034] 3. Precursor impregnation 10 mL of tetrabutyl titanate, 0.12 g of ferric nitrate, 0.09 g of cobalt nitrate, 0.09 g of nickel nitrate, 0.06 g of copper nitrate, 0.06 g of zinc nitrate, 1.0 g of 50 wt% phytic acid aqueous solution, and 0.5 g of melamine were added sequentially to 50 mL of anhydrous ethanol. After stirring evenly, the mixture was ultrasonically dispersed for 15 min at a power of 200 W and a frequency of 60 kHz. After ultrasonic dispersion, a precursor impregnation solution was obtained. ZIF-8 nanocrystalline fibers were immersed in the precursor impregnation solution at a mass ratio of 1:10. The solution was soaked at room temperature for 4 h, and then drained to obtain precursor impregnated fibers.
[0035] 4. Freeze 8g of precursor-impregnated fiber was placed in a polytetrafluoroethylene mold, 2g of deionized water was added to wet it, and then it was placed in a directional freezing device with the cold source located at the bottom of the mold. The mold was directionally frozen from bottom to top to -50℃ at a cooling rate of 5℃ / min. After freezing, the mold was transferred to a freeze dryer and freeze-dried at -60℃ and a vacuum of 5Pa for 36 hours. After freezing, frozen fiber was obtained.
[0036] 5. In-situ phosphating and carbonization The frozen fiber was placed in a dielectric barrier discharge cold plasma reactor, evacuated to 5 Pa, and an Ar / H2 mixed atmosphere was introduced at a flow rate of 60 sccm. The pressure inside the reactor was maintained at 50 Pa, and the volume fraction of H2 in the mixed atmosphere was 10%. The plasma power supply was turned on, and the plasma power inside the reactor was controlled at 100 W. The treatment time was 60 min. During the treatment, the temperature inside the reactor was controlled to be ≤400℃. After the treatment was completed, the plasma power supply was turned off, and the Ar atmosphere was continued to be introduced until the reactor cooled to room temperature. The fiber was then removed, and the magnetic photocatalytic porous carbon composite material was obtained.
[0037] Example 1: HEP nanoparticles were generated in situ under cold plasma by introducing polymetallic salts and phosphorus-containing organic compounds, while nitrogen-containing organic compounds participated in the construction of Fe-N X Single-atom sites enabled HEP and Fe-N X The coexistence of the two forms endows the material with excellent magnetic recycling performance and all-weather degradation capability.
[0038] The TiO2 shedding rate in Example 1 was 3.5%. The TiO2 shedding rate was calculated by dispersing 0.2g of magnetic photocatalytic porous carbon composite material sample in 20mL of deionized water, ultrasonicating at 200W and 40kHz for 30min, measuring the Ti concentration by ICP-OES, and then calculating the TiO2 shedding rate.
[0039] Example 2 The difference from Example 1 is as follows: In step 2, during the in-situ growth of MOFs, the static reaction time at room temperature was changed to 16 hours. In step 3, during precursor impregnation, the volume fraction of the titanium precursor in anhydrous ethanol was changed to 30%, and the amount of ferric nitrate added was adjusted to 0.20g. In step 5, the in-situ phosphating and carbonization process, the plasma power was changed to 150W and the processing time was changed to 45min. The rest is the same as in Example 1.
[0040] Example 2 shows that appropriately increasing the concentration of titanium precursor and plasma power helps to improve magnetic and Fenton-like activity, but the power needs to be controlled to prevent excessive HEP growth.
[0041] Example 3 The difference from Example 1 is as follows: In step 1, the alkali soaking was performed by replacing the paulownia wood fiber with cotton fiber that was 8 mm long and 0.3 mm in diameter; the alkali solution was replaced with a 1.5 mol / L KOH solution. In step 3, during precursor impregnation, the phosphorus-containing organic matter was replaced with 0.5g of triphenyl phosphate; The rest is the same as in Example 1.
[0042] Example 3 illustrates that KOH has a stronger activation effect, and different phosphorus sources can all effectively participate in HEP generation.
[0043] Example 4 The difference from Example 1 is as follows: In step 5, the in-situ phosphating and carbonization process, the plasma treatment time is extended to 90 min. The rest is the same as in Example 1.
[0044] Example 4 shows that extending the processing time can moderately improve the magnetic properties and Fenton-like activity, but too long a processing time may cause some micropores to fuse together, resulting in a slight decrease in specific surface area.
[0045] Comparative Example 1 The difference from Example 1 is as follows: Step 2, in-situ growth, is omitted; the alkali-impregnated fibers are directly used in the precursor impregnation step. The rest is the same as in Example 1.
[0046] In the magnetic photocatalytic porous carbon composite material obtained in Comparative Example 1, due to the lack of template and anchoring effect of ZIF-8 nanocrystals, TiO2 and HEP are randomly distributed in the carbon skeleton, and no outer gradient enrichment shell and inner HEP partition structure are formed. The chemical bonding of Ti-OP and Ti-N interfaces is reduced, and the binding force between the active components and the carbon matrix is weak. Comparative Example 1 shows that in-situ MOF growth is the key to constructing an outer layer of gradient enriched TiO2 and an inner layer of HEP partitioned synergistic structure. Without MOF, the structural order, active component anchoring strength and high salt resistance of the material are significantly reduced. The TiO2 shedding rate of Comparative Example 1 reached 25%. The TiO2 shedding rate was calculated by dispersing 0.2g of magnetic photocatalytic porous carbon composite material sample in 20mL of deionized water, ultrasonicating at 200W and 40kHz for 30min, measuring the Ti concentration by ICP-OES, and calculating the TiO2 shedding rate.
[0047] Comparative Example 2 The difference from Example 1 is as follows: Step 5, in-situ phosphating and carbonization, is changed to placing the frozen fiber in a tube furnace, heating it to 625℃ at 5℃ / min under N2 atmosphere and holding it for 2 hours. After naturally returning to room temperature, a magnetic photocatalytic porous carbon composite material is obtained. The rest is the same as in Example 1.
[0048] After carbonization in a tube furnace, HEP particles exhibit uneven size (10-100 nm) and partial agglomeration; due to the absence of a plasma reducing atmosphere, Fe–N x The content was significantly reduced; high temperature caused partial pore collapse, reducing the specific surface area and overall performance; Comparative Example 2 shows that cold plasma low-temperature simultaneous carbonization and phosphating has a significant effect on the uniform formation of HEP and Fe–N x Site formation and pore structure retention are irreplaceable, and high-temperature carbonization in tubular furnaces cannot achieve the same effect.
[0049] Comparative Example 3 The difference from Example 1 is as follows: Step 5, in-situ phosphating and carbonization, is changed to placing the frozen fiber in a muffle furnace and calcining it at 400°C for 2 hours in an air atmosphere. After naturally recovering to room temperature, a magnetic photocatalytic porous carbon composite material is obtained. The rest is the same as in Example 1.
[0050] Comparative Example 3 showed incomplete carbonization, poor hydrophobicity, low specific surface area, and low oil adsorption capacity. TiO2 was mainly in an amorphous state, Fe was not reduced to HEP, the material was non-magnetic, and there was no Fe-N. XThe formation of the product did not exhibit any microwave absorption properties; the specific surface area retention rate was low after 30 days in high-salt conditions; this indicates that low-temperature calcination cannot achieve sufficient carbonization, crystalline TiO2 formation, and in-situ HEP synthesis, further demonstrating the necessity of cold plasma reducing atmosphere and activation.
[0051] Comparative Example 4 The difference from Example 1 is as follows: In step 3, the melamine component is omitted during precursor impregnation. The rest is the same as in Example 1.
[0052] In Comparative Example 4, Fe existed only in the single form of the Fe component in HEP, without Fe-N. X Single-atom sites exhibit a degradation rate of <5% under light-free conditions, and Fenton-like activity disappears, indicating that nitrogen-containing organic matter is essential for constructing Fe-N... X The key is the single-atom site; the absence of this site results in the material losing its all-weather degradation capability, demonstrating the necessity of the coexistence of Fe dual-forms for functional synergy.
[0053] Comparative Example 5 The difference from Example 1 is as follows: Phytic acid is omitted in step 3, the precursor impregnation process. The rest is the same as in Example 1.
[0054] Comparative Example 5 revealed no HEP formation. In cold plasma, polymetallic salts mainly formed metal oxides (Fe3O4, Co3O4, etc.) rather than high-entropy phosphides. The specific surface area, oil adsorption capacity, saturation magnetization intensity, and photocatalytic degradation rate decreased. This indicates that phosphorus-containing organic matter is a key precursor for in-situ HEP formation. Its absence significantly reduced magnetic, photocatalytic, and microwave absorption properties, demonstrating the multifunctional synergistic advantages of HEP.
[0055] Comparative Example 6 The difference from Example 1 is as follows: Step 4, the freezing step, is changed to placing the precursor-impregnated fiber directly in a -50℃ freezer for 24 hours to obtain frozen fiber; The rest is the same as in Example 1.
[0056] The channels in Comparative Example 6 are randomly distributed and lack directional continuity; the specific surface area is reduced to 298 m². 2 / g, the oil adsorption rate decreased by about 50%, indicating that the directional pore formation of the frozen template is the key to constructing hierarchical channels with low mass transfer resistance. Without it, the material suffers severe channel collapse in a high-salt environment, proving the decisive role of directional channels in resisting high-salt performance.
[0057] Performance testing 1. Specific surface area, saturation magnetization The specific surface area and saturation magnetization of the magnetic photocatalytic porous carbon composite materials prepared in Examples 1-4 and Comparative Examples 1-6 were tested, and the results are as follows:
[0058] 2. Absorption performance Using a vector network analyzer, the magnetic photocatalytic porous carbon composite material samples prepared in Strong Examples 1-4 and Comparative Examples 1-6 were mixed with paraffin at a mass ratio of 1:3 and pressed into coaxial rings with an outer diameter of 7.0 mm, an inner diameter of 3.04 mm, and a thickness of 2.0-3.5 mm. The test frequency range was 2-18 GHz, and the reflection loss (RL) and effective absorption bandwidth (RL < -10 dB) were calculated. The results are as follows:
[0059] As shown in Table 3, Examples 1-4 all exhibited excellent microwave absorption performance, with Example 1 showing the best results (RL_min=-48dB, bandwidth 6.2GHz). Comparative Example 1, lacking HEP, suffered from a significant decrease in absorption performance due to the absence of magnetic loss. Comparative Example 2 experienced HEP agglomeration and impediment mismatch due to carbonization in the tubular furnace. Comparative Example 3, with incomplete carbonization, had virtually no absorption performance. Comparative Example 4 lacked bimorphic Fe, but HEP was still present, resulting in acceptable absorption performance, though lower than that of the examples. Comparative Example 5 lacked HEP and was replaced with metal oxide, leading to reduced magnetic loss. Comparative Example 6 lacked directional channels, but HEP and Fe-N were present. X Both exist, and their absorption performance is similar to that of the example, but their high-salt stability is poor.
[0060] Application performance 1. Application in marine oil spills Artificial seawater (prepared according to ASTM D1141-98 standard) was used as a solvent, and a mixture of crude oil, diesel oil, and petroleum hydrocarbons was added in a mass ratio of 5:3:2 to prepare a simulated marine oily wastewater body with a total oil concentration of 10 g / L; wherein the crude oil was API 32° light crude oil, the diesel oil was 0# automotive diesel oil, and the petroleum hydrocarbons were a mixture of C10-C20 n-alkanes; Test method: 0.5 g of each of the magnetic photocatalytic porous carbon composite materials prepared in Examples 1-4 and Comparative Examples 1-6 were added to 50 mL of the simulated marine oily wastewater. The adsorption was carried out at 25°C with constant temperature shaking for 2 h, and the adsorption capacity was measured. Subsequently, the water was irradiated for 3 h under simulated sunlight with a light intensity of 100 mW / cm² and the light source was 15 cm away from the liquid surface. The concentration of residual oil pollutants in the water was determined by infrared spectrophotometry according to HJ 637-2018 "Determination of Petroleum and Animal and Vegetable Oils in Water Quality - Infrared Spectrophotometry". The oil removal rate after photocatalysis was calculated. Each test was repeated 3 times and the average value was taken. Take 0.5 g of each of the magnetic photocatalytic porous carbon composite materials prepared in Examples 1-4 and Comparative Examples 1-6, and add them to 50 mL of the simulated marine oily wastewater. Then add hydrogen peroxide (H2O2) to make the initial concentration 5 mmol / L. After adsorption by constant temperature shaking at 25℃ for 2 h, transfer to a completely dark room environment and let stand for 3 h. Refer to HJ 637-2018 "Determination of Petroleum and Animal and Vegetable Oils in Water by Infrared Spectrophotometry" to determine the concentration of residual oil pollutants in the water by infrared spectrophotometry and calculate the oil removal rate under dark conditions. Each test is repeated 3 times and the results are taken as the arithmetic mean. The test results are as follows:
[0061] As shown in Table 1, Examples 1-4 all exhibited excellent synergistic adsorption and photocatalytic performance in marine oily environments, with oil removal rates all ≥93%. Among them, Examples 1, 2, and 5 showed particularly good performance due to their moderate HEP content and Fe-N... X It has abundant loci and optimal overall performance; Comparative Example 1 lacks HEP and Fe-N X Comparative Example 2 showed a significant decrease in performance due to the loss of magnetic properties and a substantial reduction in photocatalytic efficiency; Comparative Example 3 exhibited incomplete carbonization, poor hydrophobicity, and poor adsorption and photocatalytic performance; Comparative Example 4 lacked Fe-N... X The Fenton-like activity was lost, and the removal rate without light was <5%; Comparative Example 5 had no HEP, and the photocatalytic efficiency was reduced; Comparative Example 6 had no directional channels, and the adsorption capacity and removal rate decreased. In particular, Examples 1-4 maintained an oil removal rate of over 40% even under light-free conditions, demonstrating that Fe-N X The Fenton-like catalytic effect at the site endows the material with all-weather degradation capability, while comparative examples 1, 3, and 4 have virtually no degradation capability under light-free conditions.
[0062] 2. Application in industrial oily wastewater Industrial oily wastewater: The industrial oily wastewater contained 5.2 g / L of oil pollutants, 1200 mg / L of COD, and 0.5 mg / L of methylene blue. 0.5 g of the magnetic photocatalytic porous carbon composite material prepared in Example 1 was added to 50 mL of wastewater, and the mixture was shaken and adsorbed at 25 °C for 1 h. Then, it was irradiated with a 300 W xenon lamp simulating sunlight for 3 h with a light intensity of 100 mW / cm². 2 The light source was 15cm above the liquid surface. Various parameters were measured before and after treatment. The results are as follows:
[0063] The results show that the material of the present invention has a good treatment effect on actual industrial oily wastewater, and in particular, it exhibits a high efficiency in degrading dye pollutants.
[0064] 3. Applications in high-salt environments Test method: 0.5 g each of the magnetic photocatalytic porous carbon composite materials prepared in Examples 1-4 and Comparative Examples 1-6 were immersed in 100 mL of artificial seawater (ASTM D1141-98, salinity 35‰), left to stand at 25°C for 30 days, then washed with deionized water and dried at 60°C. The specific surface area and photocatalytic degradation rate were re-measured, and the retention rate was calculated. The results are as follows:
[0065] As shown in Table 4, after being immersed in a high-salt environment for 30 days, Examples 1-4 retained a specific surface area of ≥87%, a photocatalytic degradation rate of ≥82%, and only slightly decreased microwave absorption performance. This demonstrates that the directional channels and N / P co-doped carbon skeleton completely preserved by cold plasma low-temperature carbonization endow the material with excellent resistance to high-salt channel collapse. Comparative Examples 1, 2, and 3 showed significantly reduced retention rates due to unstable pore structure; Comparative Example 6, due to the lack of a frozen template for directional pore creation and random pore formation, suffered severe collapse under high-salt conditions, resulting in a retention rate of only 58%, further demonstrating the crucial role of directional pores in resisting high-salt performance.
Claims
1. A method for preparing a multi-level partitioned synergistic magnetic photocatalytic biomass-based porous carbon composite material, characterized in that, The preparation method includes the steps of alkaline leaching, in-situ MOF growth, precursor impregnation, freezing, and in-situ phosphating and carbonization. The MOF in-situ growth step involves immersing the alkaline-impregnated fiber in a solution containing metal salts and organic ligands to grow ZIF-8 nanocrystalline fibers in situ. The precursor impregnation step involves adding titanium precursor, multi-metal precursor, phosphorus-containing organic matter, and nitrogen-containing organic matter to a solvent, followed by ultrasonic dispersion to obtain a precursor impregnation solution. ZIF-8 nanocrystal fibers were immersed in a precursor impregnation solution, removed and drained to obtain precursor impregnated fibers. The in-situ phosphating and carbonization step involves placing the frozen fiber in a dielectric barrier discharge cold plasma reactor, evacuating it, introducing a mixed atmosphere, maintaining the pressure inside the reactor at 10-100 Pa, turning on the plasma power supply, and obtaining the magnetic photocatalytic porous carbon composite material after the treatment is completed.
2. The method for preparing a multi-level partitioned synergistic structure magnetic photocatalytic biomass-based porous carbon composite material according to claim 1, characterized in that, The alkaline impregnation step involves immersing the plant fiber raw material in an alkaline solution of 10-30 times its mass at 40-60°C for 2-5 hours. After immersion, the raw material is washed and dried to obtain alkaline-impregnated fiber. The plant fiber is one or more of the following: paulownia wood fiber, cotton fiber, hemp fiber, and straw fiber. The length of the plant fiber is 2-10 mm and the diameter is 0.1-1 mm. The alkaline solution is a sodium hydroxide or potassium hydroxide solution with a mass concentration of 4-6 wt%.
3. The method for preparing a multi-level partitioned synergistic structure magnetic photocatalytic biomass-based porous carbon composite material according to claim 1, characterized in that, In the MOF in-situ growth step, the metal salt solution is prepared by adding zinc nitrate Zn(NO3)2·6H2O or zinc acetate to anhydrous methanol and stirring until homogeneous to obtain a metal salt solution with a concentration of 0.02-0.05 mol / L. The organic ligand solution is prepared by dissolving 2-methylimidazole in anhydrous methanol to obtain an organic ligand solution with a concentration of 0.16-0.40 mol / L.
4. The method for preparing a multi-level partitioned synergistic structure magnetic photocatalytic biomass-based porous carbon composite material according to claim 1, characterized in that, In the MOF in-situ growth step, the mass ratio of the alkali-impregnated fiber to zinc nitrate is 1:0.2-0.5; The molar ratio of zinc nitrate to 2-methylimidazole is 1:4-8.
5. The method for preparing a multi-level partitioned synergistic structure magnetic photocatalytic biomass-based porous carbon composite material according to claim 1, characterized in that, In the precursor impregnation step, the titanium precursor is tetrabutyl titanate or isopropyl titanate, and the volume fraction of the titanium precursor in the precursor impregnation solution is 10%-30%. The multi-metal precursor is at least four of the following: iron salt, cobalt salt, nickel salt, copper salt, and zinc salt. Each salt is added in an equimolar ratio, and the total metal ion concentration is 0.05-0.2 mol / L. The iron salt is one of ferric nitrate (Fe(NO3)3·9H2O), ferric acetylacetone (Fe(C5H7O2)3), or ferric chloride (FeCl3·6H2O); the cobalt salt is cobalt nitrate (Co(NO3)2·6H2O) or cobalt acetate (Co(CH3COO)2·4H2O); the nickel salt is nickel nitrate (Ni(NO3)2·6H2O) or nickel acetate (Ni(CH3COO)2·4H2O); the copper salt is copper nitrate (Cu(NO3)2·3H2O) or copper acetate (Cu(CH3COO)2·H2O); and the zinc salt is zinc nitrate (Zn(NO3)2·6H2O) or zinc acetate (Zn(CH3COO)2·2H2O). The phosphorus-containing organic matter is phytic acid or triphenyl phosphate, and the amount added is 1-5% of the total mass of the precursor impregnation solution. The nitrogen-containing organic compound is urea, melamine, or polyaniline, and the amount added is 1-5% of the total mass of the precursor impregnation solution.
6. The method for preparing a multi-level partitioned synergistic structure magnetic photocatalytic biomass-based porous carbon composite material according to claim 1, characterized in that, The freezing step involves placing the precursor-impregnated fiber in a polytetrafluoroethylene mold, adding deionized water to wet the fiber surface, with the mass ratio of deionized water to precursor-impregnated fiber being 1:4-5, and then placing it in a directional freezing device with the cold source located at the bottom of the mold. Directional freezing is performed at a cooling rate of 1-10℃ / min in a direction perpendicular to the cold source, with the freezing endpoint temperature ranging from -20 to -196℃. After freezing, the mold is transferred to a freeze dryer and freeze-dried at -50℃ and a vacuum of 1-10Pa for 24-48 hours. After freeze-drying, frozen fiber is obtained.
7. The method for preparing a multi-level partitioned synergistic magnetic photocatalytic biomass-based porous carbon composite material according to claim 1, characterized in that, In the in-situ phosphating and carbonization step, the mixed atmosphere is an Ar / H2 mixed atmosphere or an Ar / NH3 mixed atmosphere; the flow rate of the Ar / H2 mixed atmosphere is 20-100 sccm, and the volume fraction of H2 is 5%-15%; the flow rate of the Ar / NH3 mixed atmosphere is 20-100 sccm, and the volume fraction of NH3 is 5%-10%. The plasma treatment has a plasma power of 50-200W and a treatment time of 30-120min.
8. A multi-level partitioned synergistic structure magnetic photocatalytic biomass-based porous carbon composite material, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.
9. The application of a multi-level partitioned synergistic structure magnetic photocatalytic biomass-based porous carbon composite material, characterized in that, The material is used for marine oil spills and industrial oily wastewater.